The NFY Transcription Factor Mediates Induction of the von Willebrand Factor Promoter by Irradiation - Bertagna, Angela; Jahroudi, Nadia (Thrombosis and Haemostasis, 2001)
Ionizing irradiation in patients is proposed to cause thrombus formation. An increase in von Willebrand factor secretion in response to irradiation is a major contributing factor to thrombus formation. We have previously reported that the increased VWF secretion in response to irradiation is mediated at the transcriptional level. The VWF core promoter fragment (sequences –90 to +22) was shown to contain the necessary cis-acting element(s) to mediate the irradiation response of the VWF gene. Here we report that a CCAAT element in the VWF promoter is the cis-acting element necessary for irradiation induction and that the NFY transcription factor interacts with this element. These analyses demonstrate that inhibition of NFY’s interaction with the CCAAT element abolishes the irradiation induction of the VWF promoter. These results provide a novel role for NFY and add this factor to the small list of irradiation-responsive transcription factors. Coimmunoprecipitation experiments demonstrated that NFY is associated with the histone acetylase P/CAF in vivo and that irradiation resulted in an increased association of NFY with coactivator P/CAF. We propose that irradiation induction of the VWF promoter involves a mechanism resulting in increased recruitment of the coactivator P/CAF to the promoter via the NFY transcription factor.
Keywords: NFY; von Willebrand factor; irradiation; promoter